Transient plant transformation mediated by Agrobacterium tumefaciens: Principles, methods and applications - Krenek, Pavel; Samajova, Olga; Luptovciak, Ivan; Doskocilova, Anna; Komis, George; Samaj, Jozef (Biotechnology advances, 2015)
Agrobacterium tumefaciens is widely used as a versatile tool for development of stably transformed model plants and crops. However, the development of Agrobacterium based transient plant transformation methods attracted substantial attention in recent years. Transient transformation methods offer several applications advancing stable transformations such as rapid and scalable recombinant protein production and in planta functional genomics studies. Herein, we highlight Agrobacterium and plant genetics factors affecting transfer of T-DNA from Agrobacterium into the plant cell nucleus and subsequent transient transgene expression. We also review recent methods concerning Agrobacterium mediated transient transformation of model plants and crops and outline key physical, physiological and genetic factors leading to their successful establishment. Of interest are especially Agrobacterium based reverse genetics studies in economically important crops relying on use of RNA interference (RNAi) or virus-induced gene silencing (VIGS) technology. The applications of Agrobacterium based transient plant transformation technology in biotech industry are presented in thorough detail. These involve production of recombinant proteins (plantibodies, vaccines and therapeutics) and effectoromics-assisted breeding of late blight resistance in potato. In addition, we also discuss biotechnological potential of recombinant GFP technology and present own examples of successful Agrobacterium mediated transient plant transformations.
Keywords: rostliny; rostlinné proteiny; Plants; biotechnologie; Plant Proteins; Agrobacterium tumefaciens; Gene Transfer Techniques; Biotechnology; technika přenosu genů; transformace genetická; Transformation, Genetic